2017
DOI: 10.1002/etc.3584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two commonly used fungicides on the amphipod Austrochiltonia subtenuis

Abstract: Fungicides are used widely in agriculture and have been detected in adjacent rivers and wetlands. However, relatively little is known about the potential effects of fungicides on aquatic organisms. The present study investigated the effects of 2 commonly used fungicides, the boscalid fungicide Filan and the myclobutanil fungicide Systhane 400 WP, on life history traits (survival, growth, and reproduction) and energy reserves (lipid, protein, and glycogen content) of the amphipod Austrochiltonia subtenuis under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
2
9
1
Order By: Relevance
“…Our results in terms of female growth and survival strongly support this hypothesis because Systhane had no effects on female head length (Table 1) and female survival (data not shown). These findings are also in agreement with our previous study showing that juvenile amphipods exposed to Systhane (0.3, 3, and 30 mg a.i./L) reached maturation later than control amphipods [28].…”
Section: Reproductionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results in terms of female growth and survival strongly support this hypothesis because Systhane had no effects on female head length (Table 1) and female survival (data not shown). These findings are also in agreement with our previous study showing that juvenile amphipods exposed to Systhane (0.3, 3, and 30 mg a.i./L) reached maturation later than control amphipods [28].…”
Section: Reproductionsupporting
confidence: 94%
“…No significant differences in mortality were observed between treatments and the control after 7 or 28 d (Figure ). Our previous work showed that both Filan and Systhane significantly reduced the survival of A. subtenuis at 10 and 0.3 μg a.i./L after 7 d of exposure, respectively . In the present study, however, no significant effects were observed at even higher concentrations (40 μg a.i./L of Filan and 3 μg a.i./L of Systhane), both singly and in combination.…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, some fungicides can have direct effects on invertebrates. For example, myclobutanil has contact toxicity for the fungivorous coccinellid Psyllobora vigintimaculata (Sutherland et al ., ) and the aquatic amphipod Austrochiltonia subtenuis (Vu et al ., ) and mancozeb can affect the fertility of the predatory mite Phytoseiulus persimilis (Ditillo et al ., ), although it has relatively low toxicity to the predatory coccinellid Halmus chalybeus (Lo, ). Nitrogen fertilizers are known to affect herbivorous insects, particularly phloem sap‐sucking species, via changes in plant quality (Butler et al ., ) and the same may hold true for leaf‐feeding detritivores.…”
Section: Discussionmentioning
confidence: 99%